An examination of kinematic parameters related to pole vault performance - Enoki, S.; Nakayama, K.; Takigawa, H.; Kuramochi, R. (International Journal of Performance Analysis in Sport, 2023)
Although various studies have examined factors associated with pole vault performance, only a few have identified a linear relationship between these factors and performance. This study aimed to identify the kinematics variables correlating with the maximum centre of gravity (CG) height. This cross-sectional study included 16 male pole vaulters and recorded their performance using four high-speed cameras at 240 Hz. The vaulters cleared the bungee bars that were set at 90% of their personal best record. The variables during pole vaulting from the touchdown of the penultimate step on the approach to the peak height of the CG were calculated. Pearson`s correlation analysis and Spearman`s rank correlation were used to test the correlation between maximum CG height and the variables. Significant correlations were observed between the maximum CG height and the six variables (grip height, approach velocity, takeoff velocity, takeoff distance, push height, and maximum vertical velocity). Grip height showed the strongest relationship, followed by push height and takeoff velocity. Pole vaulters should aim to gain a high approach velocity and grip height to increase their mechanical energy.